Faktor yang Mempengaruhi Niat Pembelian Kembali Konsumen Generasi Z pada Makanan Cepat Saji di Jakarta Barat - Deni Prasetiyo; Ritta Setiyati (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the factors that affect the purchase intention of Generation Z consumers towards fast food products in the West Jakarta area. The main focus of this study is on brand variables, food quality, service quality, and price. The research method used was quantitative with a survey approach, involving 200 respondents who were selected purposively. Data collection was carried out through questionnaire distribution, and data analysis using SPSS software version 27, including pretest test, multiple linear regression test, F test (simultaneous), and t test (partial) with a significance level of 5% (α = 0.05). The results showed that the four independent variables had a positive influence both simultaneously and partially on buyback intentions. These findings reinforce the existing literature on the importance of brand image, product quality, service, and price in shaping consumer decisions, especially in the Generation Z segment who have selective and responsive characteristics to quality and value. This research provides practical implications for fast food business actors to improve consumer experience-based marketing strategies to maintain loyalty and encourage sustainable repurchases.